The Influence of Brand Image Towards Brand Loyalty of Dental Hospital of Universitas Muhammadiyah Yogyakarta - Regia Aristiyanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
The change of hospital image become socio-economic organizations requires hospital has to be able to finance its operations and compete to gain the market share. Dental Hospital of Univesitas Muhammadiyah Yogyakarta is hospital in Yogyakarta. Hospital uses various marketing strategies to seize and retain consumer. One of them is making good brand image to get consumer loyalty. The purpose of study was to determine the influence of brand image towards brand loyalty of Dental Hospital of Universitas Muhammadiyah Yogyakarta. The type study was quantitative research with causality and descriptive explanation. The samples were dental specialist pastient of Dental Hospital of Universitas Muhammadiyah Yogyakarta who had visited more than once with quota sampling technique. Data analysis was multiple regression analysis. The results showed brand image dimensions had a positive and significant simultaneously influence toward consumer loyalty of Dental Hospital of Universitas Muhammadiyah Yogyakarta. The favorability of brand association and uniqueness of brand association had positive and significant influence towards brand loyalty, while the strength of brand association had positive and insignificant influence towards brand loyalty. The conclusion of the study showed brand image had a positive and significant influence towards brand loyalty of Dental Hospital of Universitas Muhammadiyah Yogyakarta.